Factors Linked with Prognosis in Epithelial Ovarian Cancer: A Study From Lahore, Pakistan - Rizwana Hussain, Saba Khaliq, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Current study compared prognosis variables in epithelial ovarian cancer regarding survival and expired status with follow up of 30-36 months. The variables analyzed for prognosis were age, BMI, marital status, FIGO stage, Type of tumor and parity. Identifying the factors affecting prognosis give insight of disease variation among ethnicities. Objective: It was assumed that certain factors are linked with prognosis of ovarian cancer. Therefore, the factors like age (premenopausal and postmenopausal), BMI normal (25-29) and non-normal (>30), marital status (Married and unmarried), FIGO (I-IV) stage of tumor, tumor type (Malignant and borderline) and parity status (nuliparous, primiparous, multiparous) were analyzed. Study Design: This is a Retrospective Study. Methodology: This study was conducted on 70 diagnosed epithelial ovarian cancer who were recruited for PhD research project. After the completion of study the participants were followed up after gap of (average) 30-36 months from sample collection time. Data was fetched telephonically from alive patients themselves while from first degree relatives of those who were found expired when traced. Results: This study reported non-significant impact of Age (Premenopausal, postmenopausal), BMI, tumor Type, marital status and Parity on prognosis of ovarian cancer. However, this study reported significant association of FIGO stage of tumor with prognosis of survival with p=0.016. Practical Implication: The second most frequent gynecological cancer is ovarian cancer, which has a 40% to 45% 5-year survival rate. Based on prognostic criteria, this ratio ranges from 15% to 95%.1 Prognosis is influenced by a wide range of clinical, pathological, and biological aspects. In this study, prognostic variables for advanced epithelial ovarian cancer were evaluated. Factors linked with prognosis of ovarian cancer are shown which will spread awareness in the community regarding Ovarian Cancer and bring some change in the community. Conclusion: Therefore, it was concluded that BMI, Stage of tumor, Type and Parity impose impact on life of women being diagnosed with ovarian cancer. Keywords: Ovarian cancer, prognosis, FIGO, parity, BMI, Chemotherapy, EOC, Premenopausal